Pemanfaatan Human Hair dalam Pembuatan Blending Brush Eyeshadow - Cahya Rizqi Aulia; Nurulisma Saputri; Sofia Daniati (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Makeup brushes are essential to help apply makeup. One of the commonly used brushes is the eyeshadow blending brush. Makeup brushes predominantly use synthetic base materials, but human hair can be an alternative replacement. This study aims to determine the manufacturing process, validation of product feasibility, and the level of public favourability. The process of making blending brush eyeshadow consists of the preparation stage of tools, materials, and manufacturing steps. In this study, researchers used observation, literature, experimentation, documentation, and questionnaire methods. The results of the feasibility test based on the three expert validators, validator 1 gave a score of 10 on product 1 and product 2 which means feasible, validator 2 gave a score of 12 on product 1 which means feasible and product 2 gave a score of 8 which means quite feasible, validator 3 gave a score of 12 on product 1 which means feasible and product 2 gave a score of 11 which means feasible, so it can be concluded that human hair can be used in making blending brush eyeshadow. Trials are needed to improve the texture of the hair so that it is smoother and does not hurt when used.